Vernacular Knowledge, Natural Disasters, and Climate Change in Monsoon Asia - Senjo Nakai (eTropic: electronic journal of studies in the tropics, 2021)
In Monsoon Asia, home to more than half of the world’s population, extreme climatic events are expected to become more frequent and intense due to climate change. Modern disaster management to date has focused on assessing the risks of natural hazards based on historical data, responding to disasters through prevention and mitigation techniques, and information campaigns, instead of vernacular knowledge cultivated in the local environment. This has led the public to a dangerous complacency about the power of technology over nature, and neglecting the possibility of “unforeseen” events. Climate change has not only made it more difficult to assess the risks of natural hazards, but has also diminished local resilience to them. However, since the adoption of the Hyogo Framework for Action in 2005, Monsoon Asia has begun multi-sectoral efforts to build local resilience to natural hazards by integrating vernacular knowledge into modern disaster management. Whereas in the past, experts and government agencies regarded the public as mere recipients of their services, they have now become acutely aware of the need to build partnerships with local communities to compensate for current technological limitations in disaster management, and to imaginatively prepare for the increasing risks of climatic contingencies. To achieve these goals, vernacular knowledge can be a useful resource, and a number of efforts have been initiated in the region to preserve such knowledge in imaginative forms to pass it on to future generations.